2013
DOI: 10.1016/j.mhpa.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic exercise on neurobehavioral outcomes

Abstract: Numerous studies have examined the relationship between physical activity and cognitive function, demonstrating that greater physical activity is associated with lower incidence of cognitive impairment in later life. Due to an increasingly large number of older adults at risk for cognitive impairment, the relationship between physical activity and cognition has garnered increasing public health relevance and multiple randomized trials have demonstrated that exercise interventions among sedentary adults improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 164 publications
(243 reference statements)
2
34
0
1
Order By: Relevance
“…Children also received program of 15 minutes in the form of treadmill, 15 minutes in form of stationarybicycle. Treatment was performed three times/per week for three successive months (around 36 sessions) [17] [18] and this come in agreement with Smith et.alwho reported that Different treatment strategies introduced to optimize cognition. Some of these strategies are aerobic exercises, Six months of high-intensity aerobic exercise.…”
Section: Discussionsupporting
confidence: 83%
“…Children also received program of 15 minutes in the form of treadmill, 15 minutes in form of stationarybicycle. Treatment was performed three times/per week for three successive months (around 36 sessions) [17] [18] and this come in agreement with Smith et.alwho reported that Different treatment strategies introduced to optimize cognition. Some of these strategies are aerobic exercises, Six months of high-intensity aerobic exercise.…”
Section: Discussionsupporting
confidence: 83%
“…6 Physical activity is one strategy often recommended for people with mental illness with three recent, large cross-sectional studies showing a strong association between physical activity participation and mental health. [7][8][9] Firstly, Galper et al reported an inverse dose-dependent relationship between maximal aerobic capacity and depression score measured using the Centre for Epidemiologic Studies Depression Scale (CES-D) in a sample of more than 6,000 adult men and women as part of the Aerobic Centre Longitudinal Study in the US. 7 Participants were stratified into three groups according to aerobic fitness level measured using a graded treadmill test.…”
Section: The Mental Health Benefits Of Physical Activitymentioning
confidence: 99%
“…Smith et al reported that even modest engagement in physical activity may be neuroprotective against cognitive decline in later life. 9 Their review provided evidence from numerous cross-sectional studies which demonstrate the positive dose-dependent association between overall and leisure-time physical activity, and cognitive function. In support of the findings of cross-sectional studies, this review provided evidence from a number of prospective studies.…”
Section: The Mental Health Benefits Of Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo anterior la actividad física es, a menudo, recomendada en enfermedades de índole físico y mental, para la conservación y el desarrollo de una mente sana [37,38,39]. El hecho de no haberse encontrado diferencias en todos los aspectos del componente de salud mental no indica que este ámbito no deba evaluarse.…”
Section: Discussionunclassified